Von Syrien bis Georgien - durch die Steppen Vorderasiens: Festschrift für Felix Blocher anlässlich seines 65. Geburtstages - Herles, Michael; Beuger, Claudia; Becker, Jörg; Arnhold, Simone (marru, 2021)
This festschrift is dedicated to Felix Blocher, Professor of Near Eastern Archeology at the Martin Luther University in Halle-Wittenberg, presenting 37 contributions from different fields of ancient Near Eastern cultures, regions, and epochs. Regionally, the spectrum extends from Yemen to Northwest Arabia, the Levant, Syria, Mesopotamia, Urartu, Anatolia, to Georgia and the Caucasus region; chronologically from the Uruk period of the 4th millennium, palaces of the 3rd millennium BC, through Old Babylonian cylinder seals and Neo-Assyrian tombs in Assur to the "Nineveh Court" of the first world exhibition in 1851 in Hyde Park in London and the survival of Mesopotamian gods in contemporary music. Thematically, reports on excavations are represented as well as historical, scientific-historical, and iconographic contributions.--Publisher website